A truer liberty : Simone Weil and Marxism - Blum, Lawrence A.; Seidler, Victor J. (New York : Routledge, 1989)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: Weil, Simone; kritiek; marxisme